2014
DOI: 10.2527/jas.2013-6679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lowering dietary fiber before marketing on finishing pig growth performance, carcass characteristics, carcass fat quality, and intestinal weights1,2

Abstract: A total of 264 pigs (initially 41.0 kg BW) were used in a 90-d study to determine the effects of lowering dietary fiber before market on pigs fed high dietary fiber [provided by wheat middlings (midds) and distillers dried grains with solubles (DDGS)] on growth performance, carcass characteristics, carcass fat quality, and intestinal weights of growing-finishing pigs. Pens of pigs were randomly allotted by initial BW and sex to 1 of 6 treatments with 6 replications per treatment and 7 or 8 pigs per pen. A posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
47
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 15 publications
22
47
0
Order By: Relevance
“…1, however, withdrawing these ingredients 17 d before market improved carcass yield and returned carcass weights to values similar to those of the control-fed pigs. Asmus et al (2014) also demonstrated that switching pigs from a high-fiber diet to a low-fiber diet 23 d before market allowed for full recovery of carcass yield. In agreement, Coble et al (2014) reported that removing DDGS and midds 15 to 20 d before harvest allowed carcass yield to return to levels of pigs fed corn-soybean meal-based diets throughout the finishing period.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…1, however, withdrawing these ingredients 17 d before market improved carcass yield and returned carcass weights to values similar to those of the control-fed pigs. Asmus et al (2014) also demonstrated that switching pigs from a high-fiber diet to a low-fiber diet 23 d before market allowed for full recovery of carcass yield. In agreement, Coble et al (2014) reported that removing DDGS and midds 15 to 20 d before harvest allowed carcass yield to return to levels of pigs fed corn-soybean meal-based diets throughout the finishing period.…”
Section: Methodsmentioning
confidence: 92%
“…The diets fed in Exp. 1 were similar to those used by Asmus et al (2014), who investigated the effects of reducing or completely removing DDGS and midds from finishing pig diets for multiple durations. The authors reported similar increases in ADG and ADFI when the high-fiber components were withdrawn from the diet and attributed this effect to the bulk density and energy content of the diets; that is, pigs previously fed high-fiber diets continued to consume higher volumetric amounts of feed despite switching to a more energy-dense diet.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations